Organizational Change in Distance Higher Education: the Re-negotiation of Employee's Psychological Contract - Topa, Gabriela; Morales, José. F. (Education Policy Analysis Archives, 2008)
The main purpose of this study is to explore empirical relationships of employees' attitudes towards organizational change, the perceived breach of the psychological contract and outcomes such as burnout, job satisfaction and OCB. The proposed model suggests that organizational identification will be a mediator variable in these relationships. Results of an empirical study conducted among university staff (N =150) showed that the model was an adequate fit to the data. Organizational identification mediated the relationship between psychological contract breach and outcomes while attitudes towards organizational change had a direct impact on outcomes.